Nanocomposite 3D printed resins containing titanium dioxide (TiO2) nanoparticles: an in vitro analysis of color, hardness, and surface roughness properties - AlGhamdi, Maram A.; Fouda, Shaimaa M.; Al-Dulaijan, Yousif A.; Khan, Soban Q.; El Zayat, Mai; Al Munif, Raghad; Albazroun, Zainab; Amer, Fatma Hamza; Al Ammary, Ahmed Tharwat; Mahrous, Amr A.; Gad, Mohammed M. (Frontiers in Dental Medicine, 2025)
PurposeTo investigate the effect of different titanium dioxide nanoparticle (TN) concentrations on the color stability and surface properties of additively fabricated (AF) denture base resins after thermal cycling.MethodsTwo types of AF denture base resins, NextDent and ASIGA, were used to fabricate a total of 120 disc-shaped (10 × 2 mm) specimens (n = 10). The specimens of each resin were divided into 2 groups according to the concentration of titanium dioxide nanoparticles (1 wt.%, 2 wt.% TN) in addition to a control group of pure resin for each material. The specimens’ color change, hardness, and surface roughness (Ra) were tested after thermal cycling (5,000 cycles). Collected data was analyzed using ANOVA and post hoc Tukey's test (α = 0.05). The color change was referred to the National Bureau of Standards (NBS).ResultsThe addition of TN resulted in significant color changes in NextDent, with unacceptable changes according to the NBS (8.84 for 1 wt.% TN and 8.28 for 2 wt.% TN). In contrast, ASIGA showed significantly less color change than NextDent, and the changes remained within clinically acceptable limits. For hardness, in comparison to the pure group, TN addition didn't show any significant change in terms of TN concentrations and material type (P > 0.05), and the highest hardness value was recorded with NextDent/2 wt.%TN (16.6 ± 9.0 VHN). TN addition significantly increased Ra in NextDent, which was concentration-dependent (p = 0.001), while AISGA showed no change in Ra with TN addition (p = 0.693).ConclusionNanocomposite denture base resins containing TN increased the color change and surface roughness with no change in hardness. The effect of TN was material-dependent; therefore, resin material selection for nanocomposite preparation should be considered.